2003
DOI: 10.3349/ymj.2003.44.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Features of HIV Infection/AIDS in Korea

Abstract: HIV infection/AIDS shows characteristic epidemiological and clinical patterns according to the region, country, and race. The epidemiological and clinical patterns of HIV infection/ AIDS in Korea was investigated by retrospectively analyzing the medical records of 176 HIV-infected persons who visited two major referral hospitals of AIDS in Korea from 1985 to April 2000. The most common transmission route was heterosexual contact (52.3%), followed by homosexual contact (23.9%). Among the opportunistic diseases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 0 publications
2
26
2
Order By: Relevance
“…Oocysts of C. parvum or I. belli were detected in 3.5% (4/115) and invasive amebiasis in 3.1% (6/195) of HIV-infected patients (Oh et al, 2000). With regard to PCP, our results were higher than the results previously reported in the Republic of Korea; 10.4% (18/173) or 15.9% (28/176) (Kim et al, 2003) of HIVinfected patients.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Oocysts of C. parvum or I. belli were detected in 3.5% (4/115) and invasive amebiasis in 3.1% (6/195) of HIV-infected patients (Oh et al, 2000). With regard to PCP, our results were higher than the results previously reported in the Republic of Korea; 10.4% (18/173) or 15.9% (28/176) (Kim et al, 2003) of HIVinfected patients.…”
Section: Discussioncontrasting
confidence: 78%
“…In the Republic of Korea, it was reported that 10.4% of 173 HIV-infected patients and 15.9% of 176 patients (Kim et al, 2003) developed PCP. In our study, samples for the diagnosis of P. carinii infection were collected from HIV-infected and suspected to suffer from PCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as Korean drug users can easily obtain syringes in pharmacies, only 1.1% of HIV infection is due to i.v. drug use in Korea (Kim et al, 2003). Additionally, we could not find any differences of brain volume between MA subjects and healthy comparison subjects, while patients with HIV infection have been reported to have smaller brain volumes, even in an asymptomatic state (Stout et al, 1998).…”
Section: Discussioncontrasting
confidence: 61%
“…4 Its gastrointestinal in- cell count and were classified as poor risk group as ACTG staging system according to tumor extent (T), severity of immunosuppression (I) and other systemic HIV-1-associated illness (S). 13 The most common site of gastrointestinal KS was the stomach (all cases), followed by esophagus (4 of 6 cases).…”
Section: Introductionmentioning
confidence: 99%